Integrating diverse social and ecological motivations to achieve landscape restoration. Issue 1 (20th August 2018) - Jellinek, Sacha; Wilson, Kerrie A.; Hagger, Valerie; Mumaw, Laura; Cooke, Benjamin; Guerrero, Angela M.; Erickson, Todd E.; Zamin, Tara; Waryszak, Pawel; Standish, Rachel J.
Abstract: Landscape‐scale restoration requires stakeholder collaboration and recognition of diverse social and ecological motivations to achieve multiple benefits. Yet few landscape restoration projects have set and achieved shared social and ecological goals. Mechanisms to integrate social and ecological motivations will differ in different landscapes. We provide examples from urban, agricultural, and mined landscapes to highlight how integration can achieve multiple benefits and help incentivize restoration. Better communication of ecological and especially social benefits of restoration could increase motivation. Social and economic incentives from carbon markets are evident in agricultural landscapes, biodiversity offset schemes are unlikely to motivate restoration without proof‐of‐concept, and framing restoration in terms of ecosystem services shows promise. Synthesis and applications . When setting restoration goals, it is important to recognize the diverse motivations that influence them. In doing so, and by evaluating both social and ecological benefits, we can better achieve desired restoration outcomes. Customizing incentives to cater for diverse stakeholder motivations could therefore encourage restoration projects. Abstract : When setting restoration goals, it is important to recognize the diverse motivations that influence them. In doing so, and by evaluating both social and ecological benefits, we can better achieve desired restoration outcomes. Customizing incentives to cater for diverse stakeholder motivations could therefore encourage restoration projects.